PERTUMBUHAN DAN HASIL BAWANG DAUN (Allium Fistulosum L.) PADA BERBAGAI DOSIS PUPUK KANDANG AYAM - Syamsuddin Laude; Yohanis Tambing (Agroland: Jurnal Ilmu-ilmu Pertanian, 2010)
The research aimed at identifying the effect of chicken manure doses on the growth and yield of spring onion was conducted in Wuasa village, North Lore sub district of Poso regency at ± 1100 above sea level.  The research use a Randomized Block Design consisting of 8 treatments: No fertilizer (control), 3 t fertilizer/ha (D1), 6 t fertilizer/ha (D2), 9 t fertilizer/ha (D3), 12 t fertilizer/ha (D4), 15 t fertilizer/ha (D5), 18 t fertilizer/ha (D6), and 21 t fertilizer/ha (D7).  The research results showed that 12 t chicken manures produced the largest yield for plant height and fresh plant weight.